Neonatal hypoxic-ischemic brain injury leads to sex-specific deficits in rearing and climbing in adult mice - Laštůvka, Z; Borbélyová, V; Janišová, K; Otáhal, J; Mysliveček, J; Riljak, V (Physiological research, 2020)
The study examined the morphological and long-term behavioral impacts of neonatal hypoxic-ischemic brain injury in a mouse model. We investigated the modification of different behavioral domains, such as spontaneous climbing, which represents fine motor skills. We also focused on sex-dependent differences during hypoxic-ischemic encephalopathy. The Rice-Vannucci model of hypoxia-ischemia was used, adjusted and adapted to 7-day-old C57BL/6NTac mice. The effects of induced hypoxia and ischemia were also studied separately. At postnatal day 60, mice underwent behavioral testing using the LABORAS apparatus. The perfusion for histological evaluation was performed one day after the behavioral analyses. In groups with separately induced hypoxia or ischemia, the observed alterations in behavior were not accompanied by morphological changes in the cortex or hippocampal formation. Female mice naturally climbed significantly more and hypoxic females reared less than hypoxic males (p<0.05). Male mice postnatally exposed to hypoxia-ischemia exhibited significantly lower vertical activity and higher horizontal activity (p<0.05). Mild hypoxic damage may not be morphologically detectable but may induce substantial behavioral changes in adult mice. There were significant differences between horizontal and vertical activity in reaction to hypoxia-ischemia. Our study indicates that the importance of behavioral testing is irreplaceable and may be reflected in neonatal medicine.
Keywords: Behavior, Animal; Animals, Newborn; Male; Hypoxia-Ischemia, Brain; chov zvířat; Social Isolation; poranění mozku; Brain Injuries; Biomechanical Phenomena; mužské pohlaví; mozková hypoxie a ischemie; novorozená zvířata; biomechanika; Animals; ženské pohlaví; zvířata; Animal Husbandry; myši inbrední C57BL; myši; chování zvířat; sociální izolace; Mice, Inbred C57BL; Mice; Female